Supervisory Control for Efficient Energy Management in VSC Converter-Based MVDC Microgrids with Renewable Integration (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents a novel Supervisory Control System (SCS) for a grid-connected medium-voltage DC (MVDC) microgrid that integrates renewable energy sources, battery storage, green hydrogen systems, and electric vehicle (EV) fast charging. The proposed SCS ensures power balance and enhances economic benefits by optimizing energy distribution and enabling surplus power sales to the grid. The microgrid consists of photovoltaic (PV) generation, battery storage, a green hydrogen system (including fuel cells, an electrolyzer, and a hydrogen tank), and a grid connection. Voltage Source Converters (VSCs) are utilized to adapt component output voltages to the MVDC link, minimizing the need for additional power converters. The key innovations include the MVDC configuration and the SCS framework, which efficiently manage power flow while reducing conversion losses. The system's performance is validated through simulations and hardware-in-the-loop (HIL) testing, demonstrating its effectiveness in improving operational efficiency and economic viability.
Keywords: Supervisory Control System (SCS); Medium Voltage DC (MVDC) Microgrid; Voltage Source Converter (VSC); Renewable Energy Integration; Energy Storage System (ESS)